Contrast‐Enhanced Ultrasound Examination for the Assessment of Renal Perfusion in Cats with Chronic Kidney Disease. (24th November 2017) - Stock, E.; Paepe, D.; Daminet, S.; Vandermeulen, E.; Duchateau, L.; Saunders, J.H.; Vanderperren, K.
Abstract : Background: Contrast‐enhanced ultrasound examination (CEUS) is a functional imaging technique allowing noninvasive assessment of tissue perfusion. Studies in humans show that the technique holds great potential to be used in the diagnosis of chronic kidney disease (CKD). However, data in veterinary medicine are currently lacking. Objectives: To evaluate renal perfusion using CEUS in cats with CKD. Animals: Fourteen client‐owned cats with CKD and 43 healthy control cats. Methods: Prospective case‐controlled clinical trial using CEUS to evaluate renal perfusion in cats with CKD compared to healthy control cats. Time‐intensity curves were created, and perfusion parameters were calculated using off‐line software. A linear mixed model was used to examine differences between perfusion parameters of cats with CKD and healthy cats. Results: In cats with CKD, longer time to peak and shorter mean transit times were observed for the renal cortex. In contrast, a shorter time to peak and rise time were seen for the renal medulla. The findings for the renal cortex indicate decreased blood velocity and shorter total duration of enhancement, likely caused by increased vascular resistance in CKD. Increased blood velocity in the renal medulla has not been described before and may be because of a different response to regulatory factors in cortex and medulla. Conclusions and Clinical Importance: Contrast‐enhanced ultrasound examination was capable of detecting perfusion changes in cats with CKD. Further research is warranted to assess the diagnostic capabilities of CEUS in early stage of the disease process.